Bees in Litchi Bloom: Assessing the Diversity and Foraging Behaviour of Bee Visitors in a Litchi Ecosystem (Journal of the Entomological Research Society, 2025)
A study, conducted during the litchi blooming period of 2022 and 2023, provided valuable insights into the diversity and foraging behaviour of bee visitors associated with litchi flowering in the sub-Himalayan Terai region of West Bengal. The study enlisted 15 species of bees from 5 families, namely Andrenidae (1 species), Apidae (7), Colletidae (1), Halictidae (4), and Megachilidae (2), visiting the litchi bloom. Among them, Apidae family alone contributed 49.56% of the total bee assemblage. As an individual species, Apis mellifera was the most frequent visitor (1.09 individuals/m2/minute). In contrast, Megachile laticeps was the least abundant (0.28 individuals/m2/minute) visitor with least foraging speed (2.20 seconds) and highest foraging rate (13.96 flowers/minute/forager). A good diversity of bees was ensured by the higher values of Shannon diversity (2.672) and Margalef richness (2.385) indices. Furthermore, higher value of Sheldon evenness (0.965) and lower value of Simpson dominance (0.071) indices confirmed no prominent dominance of a single/few species in the assemblage. Weather parameters like Tmax, RHmin, BSH, and wind speed had significant (p